Functional Recovery in Critically Ill Children, the "WeeCover" Multicenter Study. Issue 2 (February 2018) - Choong, Karen; Fraser, Douglas; Al-Harbi, Samah; Borham, Asm; Cameron, Jill; Cameron, Saoirse; Cheng, Ji; Clark, Heather; Doherty, Tim; Fayed, Nora; Gorter, Jan-Willem; Herridge, Margaret; et al.
Abstract : Objectives: To evaluate functional outcomes and evaluate predictors of an unfavorable functional outcome in children following a critical illness. Design: Prospective observational longitudinal cohort study. Setting: Two tertiary care, Canadian PICUs: McMaster Children's Hospital and London Health Sciences. Patients: Children 12 months to 17 years old, admitted to PICU for at least 48 hours with one or more organ dysfunction, were eligible. Patients not expected to survive, direct transfers from neonatal ICU and patients in whom long-term follow-up would not be able to be conducted, were excluded. Interventions: None. Measurements and Main Results: The primary endpoint was functional outcome up to 6 months post PICU discharge, measured using the Pediatric Evaluation of Disabilities Inventory Computer Adaptive Test. Secondary outcomes included predictors of unfavorable functional outcome, caregiver stress, health-related quality-of-life, and clinical outcomes such as mortality, length of stay, and PICU-acquired complications. One hundred eighty-two patients were enrolled; 78 children (43.6%) had functional limitations at baseline and 143 (81.5%) experienced functional deterioration following critical illness. Ninety-two (67.1%) demonstrated some functional recovery by 6 months. Higher baseline function and a neurologic insult at PICU admission were the most significant predictors of functional deterioration. Higher baseline function and increasing age were associated with slower functional recovery. Different factors affect the domains of functioning differently. Preexisting comorbidities and iatrogenic PICU-acquired morbidities were associated with persistent requirement for caregiver support (responsibility function) at 6 months. The degree of functional deterioration after critical illness was a significant predictor of increased hospital length of stay. Conclusions: This study provides new information regarding functional outcomes and the factors that influence meaningful aspects of functioning in critically ill children. Identifying patients at greatest risk and modifiable targets for improvement in PICU care guides us in developing strategies to improve functional outcomes and tailor to the rehabilitation needs of these patients and their families. Abstract : Supplemental Digital Content is available in the text.